Comportamento de cultivares de coqueiro anão (Cocos nucifera L.) nos tabuleiros costeiros do norte de Sergipe. - Castro, Cíntia Passos (2007)
Agriculture modernization, which stimulated the development of agricultural in countries like Brazil, influenced coconut palms move to unusual areas. Consequently, in order to find more adaptive crops and to reduce negative impacts on the environment, the need for awareness of the environmental influence in this plantation growth became real. With this view, this paper aimed to study the reproductive and vegetative behavior of four cultivars of dwarf coconut palms: the Malayan Yellow Dwarf (MYD), the Malayan Red Dwarf (MRD), the Cameroon Red Dwarf (CRD) and the 'Green Dwarf of Jiqui' (BGDJ) of Agreste, located in Neópolis, Sergipe. It was established a randomized block design with four treatments and four replications usind eight plants per plot. Concerning growth, flowering, fructification and fruit characterization, the following characters were analyzed: the number of alive leaves (NAL), number of emitted leaves (NEL) and the number of dead leaves (NDL); height (HS) and circumference of stipe (CS); leaf length (LL), leaflet length (LLe) and width (LW), leaflet area (LA); number of emitted inflorescences (NEI), female flowers per inflorescence (NFFI), fruits at three (NFr3) and six (NrF6) months old, fruit weight (FW) and fruit water volume (FWV). The data were submitted to analysis of variance, which was made by Sisvar program. This program compared the averages of each character and each cultivar; and GENES program estimated the heritability (h2) and genotypic (rge) and phenotypic (rfe) correlations. The cultivars have shown different vegetative and reproductive behaviors, being the BGDJ, the most adaptive cultivar for this area. Heritability was high ranging from 89,16% to 98,66%, which means that there is a high correlation between phenotypic and genotypic values. High positive phenotypic and genotypic correlations were observed for the pairs of characters NAL x NEL, NAL x NEI, NEL x NDL, NEL x NEI, NFFI x NFr3, NFFI x NFr6, NFFI x FW, NFr3 x NFr6, NFr6 x FWV, FW x FWV, expressing that the selection of a character will indirectly be selecting another; and high negative phenotypic and genotypic correlations for NEL x NFr6, NEL x FWV, SH x NFFI, SH x NFr3, SH x NFr6 e SH x FWV showing that a selection of a character may cause undesirable changes in another.